2011
DOI: 10.1177/0258042x1103600204
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocation Effect of Perceived Organizational Support on Organizational Commitment: A Study of School Teachers

Abstract: The main objective of this paper is to examine the relationship between perceived organizational support (POS) and organizational commitment of school teachers in the city of Chandigarh and Panchkula. The paper is driven theoretically by the social exchange theory, the concept of perceived organizational support (POS) which is the commitment of the organization to the employee, the norm of reciprocity, the organizational support theory as well as the other relevant literature in the human resource management a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Perceived organizational support is the general feeling and belief of individuals in this regard that the organization values cooperation, the support of its members, and is concerned about their prosperity and future (Lamastro, 1999), which creates a sense of duty toward giving importance to the organization (Luxmi & Yadav, 2011). The perception of an organization's support by employees increases the expectation that their efforts are in line with the goals of the organization and that they will be rewarded.…”
Section: Gestión Y Organizaciónmentioning
confidence: 99%
“…Perceived organizational support is the general feeling and belief of individuals in this regard that the organization values cooperation, the support of its members, and is concerned about their prosperity and future (Lamastro, 1999), which creates a sense of duty toward giving importance to the organization (Luxmi & Yadav, 2011). The perception of an organization's support by employees increases the expectation that their efforts are in line with the goals of the organization and that they will be rewarded.…”
Section: Gestión Y Organizaciónmentioning
confidence: 99%
“…As a result, teachers demonstrate a strong commitment to elevating student accomplishment. Luxmi and Yadav (2011) determine that teacher commitment as one of the most critical factors in determining the educational system's success. Like a result, teachers work hard to ensure that the instructional sessions they offer have a positive impact on their students.…”
Section: Conclusion Implication and Recommendationsmentioning
confidence: 99%
“…Colquitt et al (2015) stated commitment and job performance as primary individual outcomes that highly contributed to the organizational achievement. Teacher commitment has been identified as one of the critical factors to determine the future success of education and schools (Luxmi & Yadav, 2011). Moreover, there is a direct relationship between commitment and job performance (Cohen, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the broader impact of testing the relationship between perceived organizational support (POS) and school teachers' commitment in Chandigarh and Panchkula cities showed that they are motivated and committed to work. Therefore, all possible efforts must be conducted to develop a high level of organizational support among teachers (Luxmi & Yadav, 2011).…”
Section: Introductionmentioning
confidence: 99%